Esketamine combined with sufentanil versus sufentanil in patient-controlled intravenous analgesia: a meta-analysis - Manman Yao; Manman Yao; Baoxia Fang; Jinguo Yang; Peng Chen; Fuchao Chen; Fuchao Chen (Frontiers in Pharmacology, 2024)
Objective: Patient-controlled intravenous analgesia (PCIA) can alleviate pain to some extent, and several randomized controlled trials (RCTs) have examined the efficacy of esketamine-assisted sufentanil in postoperative PCIA. In this research, we conducted a meta-analysis of relevant RCTs to compare the effect and safety of esketamine-sufentanil versus sufentanil alone for postoperative PCIA.Methods: We systematically searched the Cochrane Library, PubMed, Embase, Web of Science, CNKI, and other libraries up to December 2023 to screen out RCTs examining the use of esketamine combined with sufentanil for PCIA. We analysed analgesia scores, sedation scores, adverse drug reactions and postpartum depression scores as outcome indicators.Results: This meta-analysis included 32 RCTs. The results of the meta-analysis were as follows. 1) Visual Analog Scale: The VAS scores at 6, 12, 24, and 48 h were lower in the esketamine-sufentanil group than in the sufentanil alone group, and significant differences were found at all time points (p < 0.05). 2) Ramsay Sedation Scale: The sedation score of the esketamine-sufentanil group at 48 h after surgery was higher than that of the sufentanil group alone [mean difference (MD) = −0.09 points, confidence interval (CI): (−0.26, −0.07), p = 0.27], but this difference was not significant (p > 0.05). 3) Safety: Compared with sufentanil alone, the incidence rates of postoperative nausea-vomiting, dizziness-headache, skin pruritus and respiratory depression were significantly lower in the esketamine-sufentanil group. 4) Postartum depression: The reduction in postpartum depression scores were significantly greater in the esketamine-sufentanil group than in the sufentanil alone group at 3 days [MD = −1.35 points, CI: (−1.89, −0.81), p < 0.00001] and 7 days [MD = −1.29 points, CI: (−2.42, −0.16), p = 0.03].Conclusion: The meta-analysis showed that the use of esketamine combined with sufentanil for postoperative PCIA could improve postoperative analgesia, alleviate postpartum depression and reduce the rate of postoperative adverse reactions, but there was no significant difference in sedation.